Analisis Penggunaan Sistem Pelacakan Menggunakan Antena Tracking Sistem - Jokoantoro Budi Solichin (Jurnal Ilmiah Teknik Informatika dan Komunikasi, 2023)
Orbital phenomena are altered by one or more external influences, such as an anomaly in the distribution of Earth's gravity, disturbances of the gravitational pull from the moon, impacts of meteors or other objects, or solar radiation pressure. Satellites make corrections by performing maneuvers controlled by stations on Earth, these maneuvers are known as north-south corrections and west-east corrections. These maneuvers use small rockets (thrusters) that are on the satellite body and the direction is set according to the correction direction. This shift in satellite trajectory results in reduced signal quality received by stations on earth, so we have to re-pointer manually to get a better signal by shifting ajimuth, elevation, and polarization, this method requires relatively long time and a high degree of accuracy.